Pathogenesis of obesity-associated cardiovascular diseases: Key role of biomolecules - Shreya Sood; Neeraj Mittal; Thakur Gurjeet Singh; Sushma Devi (Health Sciences Review, 2023)
Obesity has a significant role in the emergence of severe health disorders, associated comorbidities, and morbidity. According to epidemiological and clinical evidence, obesity has been linked to a number of heart related diseases, such as heart failure, coronary heart disease, hypertension, atrial fibrillation, stroke and cardiac arrest. The obesity is characterized by changes in adipose tissue's cell size, which interferes with the tissue's normal function. Furthermore, a variety of bioactive substances are produced and secreted by adipose tissue. Both local and systemic effects of obesity's abnormal expansion of adipose tissue, such as hypoxia, inflammation, dysregular secretion of adipokine, hypertension, improper function of mitochondria, insulin resistance, abnormal lipid/glucose metabolism, pro-inflammatory/pro-thrombotic state, as well as endothelial dysfunction results in variety of heart diseases. In this review, we will discuss various biomolecules such as hormones, genes, enzymes, receptors, cytokines, etc., involved in the mechanisms linking obesity to cardiovascular diseases, and how their regulation can be helpful in the treatment of these diseases.